2011
DOI: 10.1371/journal.pone.0017722
|View full text |Cite
|
Sign up to set email alerts
|

Single Virus Genomics: A New Tool for Virus Discovery

Abstract: Whole genome amplification and sequencing of single microbial cells has significantly influenced genomics and microbial ecology by facilitating direct recovery of reference genome data. However, viral genomics continues to suffer due to difficulties related to the isolation and characterization of uncultivated viruses. We report here on a new approach called ‘Single Virus Genomics’, which enabled the isolation and complete genome sequencing of the first single virus particle. A mixed assemblage comprised of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
115
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 46 publications
0
115
0
Order By: Relevance
“…In doing so, we highlight multiple priorities. First, it is essential to extend the current model to link increasingly strain-resolved information on microbial and viral diversity (Breitbart et al, 2002;Edwards and Rohwer, 2005;Allen et al, 2011) and interactions between viruses and their hosts (Flores et al, 2011;Deng et al, 2012;Weitz et al, 2013) the aggregated representation of virus-host interactions and nutrient feedbacks presented here (see the example of a calibrated model for dynamics including viruses of the algae Phaeocystis globosa; Ruardij et al, 2005). Strain-specific interactions also include the change in host physiology that occurs during infection, whether preceding lysis (Lindell et al, 2007;Ankrah et al, 2014) or during long-term associations with hosts, for example, lysogeny (McDaniel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, we highlight multiple priorities. First, it is essential to extend the current model to link increasingly strain-resolved information on microbial and viral diversity (Breitbart et al, 2002;Edwards and Rohwer, 2005;Allen et al, 2011) and interactions between viruses and their hosts (Flores et al, 2011;Deng et al, 2012;Weitz et al, 2013) the aggregated representation of virus-host interactions and nutrient feedbacks presented here (see the example of a calibrated model for dynamics including viruses of the algae Phaeocystis globosa; Ruardij et al, 2005). Strain-specific interactions also include the change in host physiology that occurs during infection, whether preceding lysis (Lindell et al, 2007;Ankrah et al, 2014) or during long-term associations with hosts, for example, lysogeny (McDaniel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…No-template-control MDA reactions were included to reveal any contaminating sequences and processed in parallel through 16S rRNA gene PCR analysis. These negative controls lacking a sorted cell were run in parallel to determine the relative amount and identity of contaminating bacterial DNA in the MDA reagents, a necessary standard practice in single-cell genomics due to the highly processive strand displacement activity of the phi29 DNA polymerase (71)(72)(73). Further amplification of selected MDAs to generate 100-200 μg for sequencing and archival storage was performed as described above with 150-1,500 ng of the original MDA as template.…”
Section: Methodsmentioning
confidence: 99%
“…Genotyping, as was performed during the proof-of-concept experiment 13 , is not a valid option for environmental or unknown isolates as conserved primers are not available across all viral groups. Also, background DNA synthesis or nonspecific amplification is commonly reported during amplification using the MDA reaction 14 .…”
Section: Discussionmentioning
confidence: 99%
“…We have found that reducing the redundant reads prior to assembly is necessary to obtain greater coverage 13 .…”
Section: Discussionmentioning
confidence: 99%